Analysis of Cocoa Clonal Seedlings Purity Through Deoxyribonucleic Acid (DNA) Barcoding and Random Amplification of Polymorphic DNA (RAPD) Fingerprinting - Sulistyani Pancaningtyas; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2022)
The genetic purity of a plant indicates the similarity properties between seedlings in the field and the description of the plant in the database. Identifying plant purity through a morphological approach has several drawbacks, including time efficiency and environmental factors, and the diversity is limited and inconsistent. This condition encourages the development of detection methods using DNA molecular markers. Plant identification through fingerprinting or the use of molecular markers has not been widely carried out on a commercial scale, considering the investment costs for this analysis are still quite expensive. Another method used for plant identification through DNA Barcoding by comparing variations between DNA sequences. The primers used to identify barcodes on cocoa were derived from the chloroplast genome, including rbcL and matK. This research aims to see the consistency of the rbcL primer when applied to other cocoa clones, and the analysis of the polymorphic diversity of each cocoa clone using DNA fingerprinting RAPD. This method will be tested on clones of Sulawesi 1, Sulawesi 2, ICCRI 03, and ICCRI 09, which were propagated by SE and mother plants in the field using cocoa leaf samples. The stages include DNA extraction, sequencing, and analysis of the sequencing results. The results of seedlings uniformity analysis using DNA barcoding on cocoa plants produced from in vitro propagation showed that the multiplied seeds did not show any difference in sequence with the parent plant (DR2, Sulawesi 1, Sulawesi 2, and ICCRI 09). The analysis of the diversity of cocoa clones DR 2, MCC 2, Sulawesi 1, Sulawesi 2, and ICCRI 09 through DNA Fingerprinting RAPD showed that the OPA 15 primer produced a more apparent polymorphic band than the other three primers (OPP 08, OPW 11, and M 29).